Atrazine best management practices: impact on water quality - Steele, Kelsi Lynne (Kansas State University, 2008)
Wichita, Kansas water supply is derived from multiple sources. Unfortunately, these sources are not expected to meet the future needs of the population. This predicted water shortage led to the development of the Equus Beds Recharge Project, to investigate artificial recharge as a solution to meet future water demands. This project focuses on the Little Arkansas River as a source of this recharge water. The Kansas Department of Health and Environment set a daily 3[Mu]g/L standard for the recharged water as opposed to surface waters used directly for drinking water which can't exceed a yearly average atrazine concentration of 3[Mu]g/L. During 2005, five sub-watersheds within the Little Arkansas River watershed were instrumented to collect water quality samples and measure flow rate to calculate daily contaminant loadings. Three of the sub-watersheds used atrazine best management practices (BMPs) applied to grain sorghum while the remaining two sub-watersheds maintained existing farm practices. During 2007, monitoring continued and additional atrazine BMPs were applied to corn grown in the treated sub-watersheds. During both 2006 and 2007, water quality monitoring was used to examine water quality parameters throughout the entire watershed. Watershed-scale monitoring allowed for pollutant transport patterns to emerge both spatially and temporally and indicated potential sources of the pollutants. In this particular study, atrazine and sediment loss were the two most important water quality parameters. Results from this study showed that by using BMPs the concentration of atrazine was decreased by greater than 40% in 2006 when compared to the atrazine concentration from those areas without BMPs. A 5% reduction was seen in 2007, which was due to differences in precipitation and runoff between the two years. There was no reduction in sediment losses between the treated and untreated watersheds during 2006, leading to the conclusion that additional practices would be needed to reduce sediment losses as well as any pollutants associated with sediment loss (ex nutrients absorbed to the sediments). During 2007, sediment, nitrogen, and phosphorus were 66%, 60%, and 55% lower respectively in the treated versus untreated sub-watershed. These 2007 differences were related to rainfall pattern differences in the sub-watersheds.
Keywords: Atrazine; Water Quality; Watershed Monitoring; Paired Watersheds; Environmental Sciences (0768)